Comparison of Asymmetric Dimethylarginine Levels Between Stages Three, Four, and Five Non-dialysis of Chronic Kidney Disease - Tri P Asmarawati; Widodo Widodo; M Thaha; Aditiawardana Aditiawardana; Nunuk Mardiana; Ardityo R Ardhany; Artaria Tjempakasari; Djoko Santoso; Pranawa Pranawa; Chandra Irwanadi (Acta Medica Indonesiana, 2016)
Aim: to determine the differences of ADMA level between stages 3, 4, and 5 non-dialysis of chronic kidney disease (CKD) patients at Outpatient Nephrology Clinic, Dr. Soetomo Hospital. Methods: a cross-sectional study was conducted on stage 3, 4, and 5 non-dialysis CKD patients at Outpatient Nephrology Clinic, Dr. Soetomo Hospital, Surabaya from January to February 2015. Stages of CKD were determined based on GFR estimation according to 4-variable MDRD formula. Statistical analysis of differences in the levels of ADMA in three subject groups use one-way ANOVA test. Results:seventy-five patients were included in the study. Each group consisted of 25 patients stage 3, 4, and, 5 non-dialysis patients. Mean age of stage 3, stage 4, and stage 5 non-dialysis CKD patients were respectively 57.12 years, 54.80 years and 53.68 years. The mean levels of ADMA in stage 3, stage 4, and 5 were 0.62 (0.11) IU/mL, 0.72 (0.16) IU/mL, and 0.73 (0.18) IU/mL respectively. Analysis of the differences between the groups showed significant differences in ADMA levels (p=0.04), with the highest difference between stage 3 and stage 5. Conclusion:comparison of ADMA levels showed significant differences between CKD stages and the level tends to be higher along with increase severity of CKD stages.